Mechanical and Coal Burst Breeding Mechanism of Coal Samples under True Triaxial Loading and Unloading - Wei Shen; Lin-ming Dou; Hu He (Advances in Civil Engineering)
A true triaxial loading and unloading experiment entailing “y-direction stress loading, z-direction stress unloading, and x-direction displacement fixing” of coal samples was conducted. Through analysis of the stress characteristics, fracture characteristics, and energy evolution in coal samples, the mechanical and coal burst breeding mechanisms of coal samples under true triaxial loading and unloading were revealed. The experiment found that the yield stress and peak stress of coal samples were not only affected by the initial loading and unloading of lateral stress but also had a negative exponential relationship with the ratio of the unloading rate and the loading rate (RURLR), thereby establishing the stress equation of coal samples under a true triaxial loading and unloading. There was a yield turning point in the stress-time curve of coal samples, and the difference in triaxial stress and acoustic emission before, and after, yield was significant. It was found that a high unloading rate and high initial stress are precursors to coal sample bursting. During loading and unloading, the high-energy area expanded, but its location was always fixed to within a certain area. The energy in this area was rapidly released to form a burst source when the sample was subjected to high-speed unloading. The nonbursting coal samples and the burst coal samples showed characteristic slabbing and bursting behaviours, respectively: the former corresponding to the acoustic emission energy value being two orders of magnitude lower than the latter. The research results can provide a reference for the study of mechanical behaviours and coal burst criteria in the rock surrounding a coal roadway excavation.